Design and development of a motor operated oil palm crusher for smallholder growers in Bangladesh (Progressive Agriculture, 2019)
At present oil palm growers are facing problem to extract crude palm oil in Bangladesh. Processing of palm oil categorized into various forms but basic processing stages are essentially the same including harvesting, sterilization, bunch stripping, digestion, crushing, clarification and drying. Extracting of palm oil is very difficult by traditional method and oil recovery rate is very low. Although mechanical processing is costly but produces good quality Crude Palm Oil (CPO) and oil recovery rate is high. An electric motor operated oil palm crusher was designed and developed and tested in laboratory under the Department of Farm Power and Machinery, Bangladesh Agricultural University, Mymensingh for processing of crude palm oil from fresh fruit bunch. The crusher was designed by using Auto-Cad software. It was fabricated according to design parameters. The major parts of the crusher were screw shaft, cylinder, hopper, hollow bars, pressure case cap, jamnut and frame which were fabricated by mild steel (MS), ball bearing, gear and pinion, line and idle shaft and spring were fabricated by carbon steel (CS) whereas driver and driven pulley were fabricated by cast iron(CI). Crusher was mounted on the frame. A 9 hp electric motor was used as a power source. Crusher was tested after fabrication and 3000 gm fresh fruits were used. About 700 gm crude palm oil, 800 gm oil cake, 1400 gm skum were collected from 2700 gm pretreated fruits. The crushing capacity and crude oil percentage of the crusher was 6.49 kg/hr and 25.93%, respectively. Rotating speed of screw was 40 rpm for smooth running. The weight of crusher was only 70 kg which is easy to operate by single person. The developed oil palm crusher may fulfill the demand of smallholder growers to extract oil from fresh fruit bunches.Progressive Agriculture 30 (1): 141-149, 2019